2017
DOI: 10.1016/j.celrep.2017.04.059
|View full text |Cite
|
Sign up to set email alerts
|

The Intergenic Recombinant HLA-B∗46:01 Has a Distinctive Peptidome that Includes KIR2DL3 Ligands

Abstract: Summary HLA-B*46:01 was formed by an intergenic mini-conversion, between HLA-B*15:01 and HLA-C*01:02, in South-East Asia during the last 50,000 years and has since become the most common HLA-B allele in the region. A functional effect of the mini-conversion was introduction of the C1 epitope into HLA-B*46:01, making it an exceptional HLA-B allotype that is recognized by the C1-specific natural killer cell receptor KIR2DL3. High-resolution mass spectrometry showed that HLA-B*46:01 has a low diversity peptidome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 78 publications
(128 reference statements)
0
43
0
Order By: Relevance
“…Hugo Hilton presented his high resolution mass spectrometry peptide analysis of the intergenic recombinant HLA-B*46:01, showing that its recent increase in South-East Asia may relate to its ability to provide ligands for C1-specific KIR and its distinctive peptide repertoire. 6 Malcolm Sim showed that KIR2DL3 binding to HLA-C1 was more peptide-dependent than KIR2DL1 binding to C2, providing a possible explanation for why KIR2DL3-C1 interactions appear weaker than KIR2DL1-C2 interactions. 7 The peptide selectivity of KIR2DL3-C1 interactions may be important in cancer cell recognition because the peptides in the cancer cell may differ from those that shape NK cell education in resting state.…”
Section: Kir Structure and Peptidesmentioning
confidence: 99%
“…Hugo Hilton presented his high resolution mass spectrometry peptide analysis of the intergenic recombinant HLA-B*46:01, showing that its recent increase in South-East Asia may relate to its ability to provide ligands for C1-specific KIR and its distinctive peptide repertoire. 6 Malcolm Sim showed that KIR2DL3 binding to HLA-C1 was more peptide-dependent than KIR2DL1 binding to C2, providing a possible explanation for why KIR2DL3-C1 interactions appear weaker than KIR2DL1-C2 interactions. 7 The peptide selectivity of KIR2DL3-C1 interactions may be important in cancer cell recognition because the peptides in the cancer cell may differ from those that shape NK cell education in resting state.…”
Section: Kir Structure and Peptidesmentioning
confidence: 99%
“…Consistent with the structural picture, KIR2DL2/3 shows greater peptide selectivity than KIR2DL1 (Sim et al 2017). Supporting this finding, our examination of endogenously processed peptides from C1 + HLA-C and HLA-B showed that <25% of the peptides are strong KIR2DL3 ligands (Hilton et al 2017b). The peptide selectivity of KIR2DL2/3 was further highlighted by the observation that peptide positions other than P7 and P8 have potential to influence the recognition of C1 + HLA-C (Hilton et al 2017b; Sim et al 2017).…”
Section: Introductionmentioning
confidence: 72%
“…Supporting this finding, our examination of endogenously processed peptides from C1 + HLA-C and HLA-B showed that <25% of the peptides are strong KIR2DL3 ligands (Hilton et al 2017b). The peptide selectivity of KIR2DL2/3 was further highlighted by the observation that peptide positions other than P7 and P8 have potential to influence the recognition of C1 + HLA-C (Hilton et al 2017b; Sim et al 2017). That KIR2DL3 appears as the receptor with the most peptide selectivity provides a compelling rationale for the observation that KIR2DL3 binding to C1 + HLA-C is weaker than KIR2DL1 binding to C2 + HLA-C (Moesta et al 2008).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Allelic variants predominantly differ by single nucleotide polymorphisms (SNPs) or insertion/deletions (indels), however, novel alleles can be generated by homologous recombination mechanisms. Recombination can involve alleles at the same locus (ie, intra‐locus recombination for example, HLA‐B*50:51 derived from HLA‐B*50:01:01:02 and HLA‐B*14:02:01 ) or alleles at different loci (ie, inter‐locus recombination for example, HLA‐B*46:01 derived from HLA‐B*15:01 and HLA‐C*01:02 ).…”
Section: New Allele Alertmentioning
confidence: 99%